Fuzzy Inference System In Predicting Unemployment Rate In City X Using Sugeno Method - Yosdarso Afero (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
Unemployment in Indonesia is currently increasing. This can be seen from the number of unemployed and workers who are looking for job vacancies either directly or through applications. The problem in this study is the lack of understanding of job applicants about the terms or criteria for applying for a job so that they are not accepted in a company. There are five criteria that must be considered in applying for a job, namely, education, vacancies, age, opportunities and knowledge. The purpose of this study is to help job seekers to complete and understand the criteria that have been set. This study uses the Sugeno method with the final result in the form of linear or constant. The working process of the Sugeno method is fuzification, inference engine, application of implication and defuzzification functions to obtain results in accordance with the decision-making system.